(untitled) (Raparin Journal of Humanities (RJH), 2024)
The brain is the main organ of the human nervous system, and one of the diseases that affect the brain is Parkinson’s disease, in most cases we see a loss of balance in Parkinson’s disease, so that the paralyzed member could not perform the required voluntary movements and this matter causes imbalance for the patient’s person and with age and degree of injury may lead to a decrease in balance. Parkinson’s disease may affect many daily activities, and treatments aim to alleviate these problems by helping you receive the knowledge and skills you need to continue doing all your previous activities, and sports rehabilitation consists in learning to move more naturally and with less effort. In this context, technological means are a tool to help achieve the objectives of the rehabilitation process. As we know that video games are an important and major part of technology in the modern life of humans, especially in the scope of rehabilitation for people with special intellectual - motor needs, and video games can be used in the rehabilitation process for these people to develop their motor skills throughout the stages of the game. It concludes from the research that the rehabilitation program using (mental exercises and video games) played a positive role to improve the skill of fixed balance and motor in the research sample and that mental exercises contributed well to improving balance in patients with type II.